2016
DOI: 10.5483/bmbrep.2016.49.2.232
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial oxidative phosphorylation complexes exist in the sarcolemma of skeletal muscle

Abstract: Although proteomic analyses have revealed the presence of mitochondrial oxidative phosphorylation (OXPHOS) proteins in the plasma membrane, there have been no in-depth evaluations of the presence or function of OXPHOS I-V in the plasma membrane. Here, we demonstrate the in situ localization of OXPHOS I-V complexes to the sarcolemma of skeletal muscle by immunofluorescence and immunohistochemistry. A portion of the OXPHOS I-V complex proteins was not co-stained with MitoTracker but co-localized with caveolin-3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 34 publications
0
14
1
Order By: Relevance
“…The mitochondrial OCR and ECAR were analyzed using an XF24 Extracellular Flux Analyzer (Seahorse Bioscience, Santa Clara, CA, USA) as described previously (Lee et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…The mitochondrial OCR and ECAR were analyzed using an XF24 Extracellular Flux Analyzer (Seahorse Bioscience, Santa Clara, CA, USA) as described previously (Lee et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…The HEK 293 cell line and C2C12 myoblasts were maintained as previously described 22 . Briefly, HEK 293 cells and C2C12 myoblasts were grown in DMEM supplemented with 1% penicillin/streptomycin and 10% fetal bovine serum in a 5% CO 2 incubator at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…The Chemiosmotic Theory (Mitchell, 1961) as it was formulated is a process that can only take place in organelle possessing double membrane systems forming closed compartments to entrap protons, such as mitochondrial cristae, bacteria and thylakoids. Here, for the sake of simplicity, we have considered the mitochondrial inner membrane, even though in recent years, it has been shown that the oxidative phosphorylation (OXPHOS), coupled to aerobic ATP synthesis, also occurs in extra-mitochondrial districts, as rod outer segment (OS ) disks (Calzia et al, 2014) (Calzia et al, 2013) (Bianchini et al, 2008) (Panfoli et al, 2009), myelin sheath (Ravera et al, 2009) (Ravera et al, 2011b) (Morelli et al, 2011) (Ravera et al, 2015), plasma membrane (Mangiullo et al, 2008) (Arakaki et al, 2003) (Arakaki et al, 2007 (Adriano et al, 2011) (Chang et al, 2012) (Lee et al, 2016) (Taurino & Gnoni, 2018) (Taurino et al, 2016) (Gao et al, 2017) extracellular vesicles shedding form cells, such as exosomes and microvesicles, which seem to carry an unsuspected metabolic signature (Panfoli et al, 2016). In particular, recent data indicate an active extramitochondrial OXPHOS in the endoplasmic reticulum of platelets which both have elevated ATP need but possess very little mitochondria (Ravera et al, 2018).…”
Section: Extramitochondrial Oxidative Phosphorylationmentioning
confidence: 99%
“…In fact, it was demonstrated that many biological membranes, devoid of closed compartments and of mitochondria, conduct OXPHOS with high efficiency (Calzia et al, 2010) (Roehlecke et al, 2013) (Mangiullo et al, 2008) (Panfoli et al, 2012) (Ravera et al, 2011b) (Ravera et al, 2013) (Ravera et al, 2018) , challenging the idea that it is exclusive of mitochondria, thylakoid and bacteria. Of particular interest are the reports of the ability of plasma membranes to synthesize ATP outside the cell, as they harbour the five complexes of respiration (Mangiullo et al, 2008) (Arakaki et al, 2003) (Arakaki et al, 2007) (Adriano et al, 2011) (Chang et al, 2012) (Lee et al, 2016).…”
Section: Introductionmentioning
confidence: 99%